Legal status of Cannabidiol - Blebea, Nicoleta Mirela (Technium BioChemMed, 2022)
The plant Cannabis sativa L., is a dioecious species belonging to the familie Cannabaceae, natived to Central Asia, with a long history. The first data on the use of this plant date from 2500 BC [1]. In Europe, the plant began to be cultivated between the 14th and 15th centuries, during which time it played an important role in agriculture, helping economic growth. In the Western world, it was increasingly used in nineteenth-century medicine [2]. It was cultivated worldwide in the 18th and 19th centuries as a source of fiber, food and oil. The main ingredients of hemp oils are phytocannabinoids such as cannabidiol (CBD) and terpenoids. The main active compound in the plant is d-9-tetrahydrocannabinol (D-9-THC), which is largely responsible for the psychoactive effects that made Indian hemp famous. While d9-THC has returned to the attention of researchers, other constituents of cannabis, such as CBD, have been studied in recent years for its therapeutic uses [3]. Hemp has gained substantial attention in recent years due to the fact that an increasing number of countries legalized Cannabis for medicinal and recreational use. Taking into account the current legislation, there are small differences in the amounts of THC allowed in hemp preparations, ranging from 0.05 to 0.6%. As a result, if the plant contains THC it has a high illicit use and interest, therefore its cultivation is prohibited by national laws [4]. Among the illicit cannabis preparations, we can mention the following: marijuana (a mixture of leaves, flowers and seeds of the hemp plant), hashish (obtained from unfertilized buds) and also oils that can be easily prepared [5]. Globally, the use of cannabis-derived preparations in the medical field has a long history. In the twentieth century, consumption became limited until March 30, 1961, when the Cannabis plant and cannabinoids were classified in the Single UN Convention as non-medical substances. In recent years, however, patients' interest in the use of cannabinoids has increased [6]. CBD, the main phytocannabinoid obtained from Cannabis sativa, brings new hope to patients suffering from a wide range of conditions: pain, inflammation, epilepsy, sleep disorders, multiple sclerosis, anorexia, schizophrenia, cancer.